2020
DOI: 10.3390/genealogy4010009
|View full text |Cite
|
Sign up to set email alerts
|

Reconnecting Rural Native Hawaiian Families to Food through Aquaponics

Abstract: Food insecurity is a pressing issue in Hawai‘i as the vast majority of available and accessible foods are imported. To address this issue, a backyard aquaponics program was implemented from 2010 to 2016 to offer additional avenues to food sovereignty in a rural predominantly Native Hawaiian community. Aquaponics provides a contained and sustainable food production system that models Native Hawaiian principles of land and water stewardship. The purpose of this community-engaged study was to identify the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Findings from this study also emphasize the importance of sustaining relationships between kānaka (people, human beings), 'āina, and akua as a way of fostering health of Hawaiians (Chun, 2008;Kūkulu Kumuhana Planning Committee, 2017;McGregor et al, 2003). As demonstrated in Table 2, these findings align with the existing literature that focus on Hawaiian health in addition to food security and food sovereignty in Hawai'i and in other Indigenous communities (Beebe et al, 2020;Delormier et al, 2017;Ho-Lastimosa et al, 2019;Kuhnlein, 2012;Sowerwine et al, 2019). The right to be well and have access to adequate and healthful foods that is respectful of one's culture is a fundamental human right.…”
Section: Discussionsupporting
confidence: 77%
“…Findings from this study also emphasize the importance of sustaining relationships between kānaka (people, human beings), 'āina, and akua as a way of fostering health of Hawaiians (Chun, 2008;Kūkulu Kumuhana Planning Committee, 2017;McGregor et al, 2003). As demonstrated in Table 2, these findings align with the existing literature that focus on Hawaiian health in addition to food security and food sovereignty in Hawai'i and in other Indigenous communities (Beebe et al, 2020;Delormier et al, 2017;Ho-Lastimosa et al, 2019;Kuhnlein, 2012;Sowerwine et al, 2019). The right to be well and have access to adequate and healthful foods that is respectful of one's culture is a fundamental human right.…”
Section: Discussionsupporting
confidence: 77%
“…Due to the coupled characteristic of these systems, practitioners are limited to biological control of pest (FAO, 2014). Beebe et al (2020) identified technological challenges among the non-expert participants as controlling pests and bugs; fish management (overpopulation); and water quality (pH and temperature). Maintaining an optimal biomass ratio and the correct feed rate ratio is critical to keep the appropriate nitrate balance of the system.…”
Section: (B) Barriers To Adoptionmentioning
confidence: 99%
“…Backyard aquaponics offers itself as a potential health intervention because of the symbiotic relationships between fish and plants creating a sustainable food production system. Culturally, the system metaphorically reflects the reciprocal caretaking model of the ahupua'a, the traditional Hawaiian land management system (Beebe et al 2020).…”
Section: Pacific Islander Responses To Settler Colonialism and Enviromentioning
confidence: 99%
“…From the WPRH, the Waimānalo Limu Hui was created, which has been working not only on limu restoration, but also the restoration of Pāhonu, a fishpond left by the ancestors of this region. Through projects like these, participants reported a greater sense of community connectedness, land stewardship, and health in their eating habits, all while being able to embrace their cultural heritage and engage in efforts of addressing food insecurity (Beebe et al 2020).…”
Section: Pacific Islander Responses To Settler Colonialism and Enviromentioning
confidence: 99%